Values in Meaning of the Binjai Tree as a City Nomenclature: A Local Wisdom Study - Baihaqi Siddik Lubis; Mamat Supriatna; Selamat Husni Hasibuan (Journal of Innovation in Educational and Cultural Research, 2025)
Local wisdom has worked as an illustration for teaching values. Little is known, nonetheless, regarding the value of the Binjai tree as a place term when teachers teach value education outside of the learner's local setting, causing them to lose awareness of it. This study aims to identify the value contained in the Binjai tree as the name of Binjai City. The research uses a literature study, sourcing data from articles searched in the Google Scholar database. Data analysis techniques include data reduction, presentation, conclusion drawing, and verification. The study uses NVIVO 12 Plus to code nodes and cases. Results show historical value, which is the nomenclature of the city. In addition, there is also socio-cultural value in Binjai trees, which are used as consumption and health materials. Binjai trees also have economic value, as tree trunks are used as building materials, and Binjai fruit is processed as a product. The study emphasizes the importance of value education through the Binjai tree in cultivating democratic, nationalist, and self-identity citizens. The implications of this study extend to learning planning, encouraging teachers to use culturally relevant local educational resources, and building a foundation for extracurricular activities that promote local wisdom heritage.